218k views
1 vote
How do you solve -y +28 +y^2 =2y +2y^2 for y?

User Limco
by
4.7k points

1 Answer

2 votes

We are given the following:

Solve for y.


-y+28+y^2=2y+2y^2

This being said, lets begin.

~~~~~~~~~~~~~~~~~~~~~~~

1. First, move
2y^2 to the left side.


-y+28-y^2=2y

2. Move
2y to the left side.


-y^2-3y+28=0

3. Solve with the quadratic formula.


y_(1,2) = (-(-3) -+ √((-3)^2-4(-1)*28) )/(2(-1))

4.
√((-3)^2-4(-1)*28)=11


y_(1,2) =(-(3)-+11)/(2(-1))

5. Separate the solutions.


y=(-(-3)+11)/(2(-1)) , y_(2) =(-(-3)-11)/(2(-1))

6.


y=(-(-3)+11)/(2(-1))
=-7First Solution

7.


y=(-(-3)-11)/(2(-1)) =4Second Solution

Final Solution:


y=-7,y=4

Hope this helps!

User Poppertech
by
4.6k points